2019
DOI: 10.1186/s12870-019-1731-0
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq and iTRAQ reveal multiple pathways involved in storage root formation and development in sweet potato (Ipomoea batatas L.)

Abstract: Background Sweet potato ( Ipomoea batatas L.) is the sixth most important food crop in the world. The formation and development of storage roots in sweet potato is a highly complicated and genetically programmed process. However, the underlying mechanisms of storage root development have not yet been elucidated. Results To better understand the molecular mechanisms involved in storage root development, a combined analysis of the transcriptome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 41 publications
8
91
1
Order By: Relevance
“…The GO and KEGG pathway analysis showed the complexity of molecular mechanisms in response to salt stress during the seed germination stage. The correlation between the transcriptome and proteome profiles varies with species, response environments, and different stages of growth and development [34][35][36]. In this study, the r values indicated a weak correlation between the transcriptome and proteome profiles under salt stress.…”
Section: Discussionmentioning
confidence: 53%
“…The GO and KEGG pathway analysis showed the complexity of molecular mechanisms in response to salt stress during the seed germination stage. The correlation between the transcriptome and proteome profiles varies with species, response environments, and different stages of growth and development [34][35][36]. In this study, the r values indicated a weak correlation between the transcriptome and proteome profiles under salt stress.…”
Section: Discussionmentioning
confidence: 53%
“…Our transcriptome data showed 9 AP2-EREBP TFs were upregulated during the process of tuberous root development, especially at the late stage ( Fig. 3 [11]. In this study, obvious changes were detected in the expression of genes related to auxins, CKs, GA, ABA, ethylene, JA and BRs in TRs, and majority of these genes were up-regulated in more than one tuberous development stage (Table 2 and Additional file 11: Table S6).…”
Section: Discussionmentioning
confidence: 57%
“…The initiation and development of storage roots constitute a highly complicated process that involves multiple pathways, which regulate the development of secondary anomalous cambia and the accumulation of starch, sucrose and other chemical components [11]. Accordingly, our study showed that carbohydrate metabolism, which mainly involved metabolic pathways (ko01100), starch and sucrose metabolism (ko00500) and biosynthesis of secondary metabolites (ko01110), was identified to the most important pathway during tuberous root development ( Fig.…”
Section: Multiple Pathways Are Activated In Regulating the Initiationmentioning
confidence: 78%
See 2 more Smart Citations